2015
DOI: 10.1155/2015/491017
|View full text |Cite
|
Sign up to set email alerts
|

Changes over Time in Intracranial Air in Patients with Cerebral Air Embolism: Radiological Study in Two Cases

Abstract: Cerebral air embolism can be easily identified on computed tomography (CT) scans. However, changes in the distribution and amount of intracranial air are not well known. We report two patients with cerebral air embolism and present imaging findings on the serial changes in the intracranial air. We thought that the embolic source was venous in one patient because CT showed air inflow in cortical veins in the bilateral frontal areas, reflecting air buoyancy. In the other patient, CT showed air inflow into not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…In our case, MRI revealed multiple infarcts in the cortical area. Other studies have reported similar MRI findings in cases with cerebral venous air embolism [6,7]. Cerebral infarcts are often observed in the cortical area near air bubbles [6].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In our case, MRI revealed multiple infarcts in the cortical area. Other studies have reported similar MRI findings in cases with cerebral venous air embolism [6,7]. Cerebral infarcts are often observed in the cortical area near air bubbles [6].…”
Section: Discussionsupporting
confidence: 53%
“…Intravascular air can lead to both arterial and venous infarcts [6]. In our case, MRI revealed multiple infarcts in the cortical area.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Arterial and venous air emboli usually affect the frontal and parietal lobes. However, it has been described that in arterial air emboli, punctate air emboli can be found in the brain parenchyma, trapped in arterial capillaries [ 14 ]. Most patients with a clinical suspicion of ischemic stroke require a noncontrast brain MRI.…”
Section: Discussionmentioning
confidence: 99%